KELAHIRAN MUHAMMADIYAH DARI PERSPEKTIF HERMENEUTIK - Suwarno Suwarno (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2019)
This article discusses the birth of Muhammadiyah from a hermeneutic perspective, especially from Gadamer. Ahmad Dahlan founded Muhammadiyah on 18 November 1912 based on the knowledge of the idea of modern Islamic reform and understanding and concern about the real condition of Muslims who was hit by poverty, ignorance and backwardness. Ahmad Dahlan has a high historical awareness to change the traditions of society which were covered by the syncretic Islamic tradition that produces superstitious culture and traditionalist Islam that produces heretical and khurafat cultures towards Islamic purification and the dynamism of Islamic society. Ahmad Dahlan's historical awareness was sustained by his strong temperament, firm stance and his courage to break the tradition of perverts.